Pd-catalyzed reductive cleavage of N-N bond in dibenzyl-1-alkylhydrazine-1,2-dicarboxylates with PMHS: application to a formal enantioselective synthesis of (R)-sitagliptin - Dey, Soumen; Gadakh, Sunita K.; Ahuja, Brij Bhushan; Kamble, Sanjay P.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
An environmentally benign approach involving Pd-catalyzed reductive N-N bond cleavage in dibenzyl-1-alkylhydrazine-1,2-dicarboxylates leading to the synthesis of N-(tert-butoxy)carbamates under very mild conditions has been described. PMHS serves as an inexpensive source of hydride in MeOH/deionized H2O medium. This protocol has been successfully applied in the formal synthesis of (R)-sitagliptin, an anti-diabetic drug. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: anti-Diabetic; Environmentally benign; Hydrazine; PMHS; Reductive cleavage